Solution
a=y
b=x+y
c=x
Hence;
"b^2-4ac=x^2-2xy+y^2=(x-y)^2>0"
So the PDE is hyperbolic and we solve as follows;
Take ;
"ar_x^2+br_xr_y+cr_y^2=0"
"yr_x^2+(x+y)r_xr_y+xr_y^2=0"
Factor;
"r_x(yr_x+xr_y)+r_y(yr_x+xr_y)" =0
"(yr_x+xr_y)(r_x+r_y)=0"
Since s also satisfies the same equation ,we take;
"yr_x+xr_y=0"
Which gives ;
"r=x^2-y^2"
"s_x+s_y=0"
Which gives;
"s=x-y"
Calculate the first derivatives;
"Z_x=2xZ_r+Z_s"
"Z_y=-2yZ_r-Z_s"
Calculating the second derivatives;
"Z_{xx}=4x^2Z_{rr}+4xZ_{rs}+Z_{ss}+2Z_r"
"Z_{xy}=-4xyZ_{rr}-2xZ_{rs}-2yZ_{rs}-Z_{ss}"
"Z_{yy}=4y^2Z_{rr}+4yZ_{rs}+Z_{ss}-2Z_r"
Substitute to the given questions to obtain;
"4x^2yZ_{rr}+4xyZ_{rs}+yZ_{ss}+2yZ_r-4x^2yZ_{rr}-2x^2Z_{rs}-2yxZ_{rs}-xZ_{ss}-4xy^2Z_{rr}-2xyZ_{rs}-2y^2Z_{rs}-yZ_{ss}+4y^2xZ_{rr}+4yxZ_{rs}+xZ_{ss}-2xZ_r"
Simplify to obtain;
"2xZ_r-2yZ_r+2x^2Z_{rs}+2y^2Z_{rs}-4xyZ_{rs}"
Divide by 2 and factorise to obtaining;
"(x-y)^2Z_{rs}+(x-y)Z_r=0"
But x-y=s
By substitution;
"s^2Z_{rs}+sZ_r=0"
Rewrite as;
"Z_{rs}+\\frac1sZ_r=0"
Comments
Leave a comment